Helping Special Needs Children to Make Friends - Anis Ernawati (Jurnal Psikiatri Surabaya, 2024)
Introduction: Children with special needs are often considered to be cursed. They are frequently ostracized from society thus making them feel lonely. This paper aims to help patients, especially children with special needs, find good friends through the review of current studies. Methods: This study used a descriptive quantitative method and data that was retrieved from Child and Adolescence Psychiatric Outpatients Daycare, Dr. Soetomo General Academic Hospital, Surabaya with 80 children with ADHD and 160 children with ASD. Results: A common intervention used in Indonesia is applied behavior analysis (ABA), a method that trains children to have social skills such as how to communicate, interact, and express themselves in social settings. Besides personal intervention, the need for integrated care for children with special needs such as pharmacological therapy, speech and behavioral therapy, occupational therapy, and special education, is needed to support them in helping them make friends. Conclusion: To help children with special needs make friends, we can give support, appreciation, and motivation. However, children with special needs need different treatment from their peers, so special attention and understanding are needed so that children with special needs can socialize and make friends well. Keywords: Children, Special Needs, Friends, Mental Health, Loneliness